Corrosion susceptibility of Zn-Al alloys with different grains and dendritic microstructures in Nacl solutions - Ares, Alicia Esther (2012)
The objective of the present research was to study the corrosion susceptibility of different hypoeutectic (Zn-1. wt.%Al, Zn-2. wt.%Al, Zn-3. wt.%Al, Zn-4. wt.%Al) and hypereutectic (Zn-16. wt.%Al, Zn-27. wt.%Al Zn-50. wt.%Al, Zn-96. wt.%Al, and Zn-98. wt.%Al) zinc-aluminium alloys with different grains (columnar, equiaxed and columnar-to-equiaxed transition, CET) and dendritic microstructures in 3% NaCl solution at room temperature.The corrosion resistance was analyzed by electrochemical impedance spectroscopy (EIS) as a principal technique. The EIS results show that as the aluminium content increases the rate of formation of corrosion products on the alloys also increases. These products appear to have protective features in the light of the results of voltammograms.